The Picture of Snow White - Krøgholt, Ida (Peripeti, 2017)
As reality theater The Picture of Snow White (1994) demonstrates how certain fragments of reality can function as the material of the performance, and at first glance The Picture of Snow White resembles the readymade’s approach to form.